#### Answer

-2

#### Work Step by Step

Using the rules of exponents, we find:
$$ 3\cdot \:9^{-x}=243 \\ 9^{-x}=81 \\ -x=2 \\ x=-2$$
Note, this can be solved since we know that:
$$ 9 ^ 2 = 81$$

Chegg costs money, GradeSaver solutions are free!

Published by
McDougal Littell

ISBN 10:
0618595414

ISBN 13:
978-0-61859-541-9

-2

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.